Rancangan Penjadwalan Produksi Brankas Dengan Metode Heijunka Di PT. Chubb Safes Indonesia - Sopian Maulana; Nunung Nuhasanah (Universitas Al Azhar Indonesia, 2021)
PT. Chubb Safes Indonesia (PT. CSI) is a company engaged in manufacturing and producing safety products for the public. In carrying out safe production, there is often a difference between the production plan made by the production department and the actual production done by the operator on the production floor. From the production plan that has been made, on the week-6 to week-8 from PT. CSI is only 76% to 89% of the production plan achieved. PT. This CSI has a FIFO (First In First Out) scheduling system and implements a mixed production system. Based on the problems experienced by PT. CSI, this can be minimized by predicting demand using the single moving average and single exponential smoothing method then the best demand prediction is obtained based on the value of the smallest deviation using the Mean Absolute Error (MAE) method where the results are obtained in the next week or the 11th week. PT. CSI can produce as many as 472 units of safes in one week. And by scheduling production using the heijunka method PT. CSI can perform 472 safe productions within 75 working hours of the available 88 working hours resulting in an efficiency of 15%. Then PT. CSI can increase daily production capacity from 424 units in the week-8 to 554 units of safes or 92 units of safes per day.Keywords – Demand prediction, Production scheduling, Heijunka method, Single moving average, Single exponential smoothing, Mean absolute error